INEQUALITY AND WELFARE OF THE DISPLACED HOUSEHOLDS DUE TO THE CONSTRUCTION OF KOTO PANJANG DAM - Fery Andrianus; Syafruddin Karimi; Werry Darta Taifur; Endrizal Ridwan (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2019)
Displacement due to the construction of the Koto Panjang dam has an impact on household welfare. The displaced households experienced a very poor economic condition at the beginning of the displacement period. This study seeks answers to two questions: how the current welfare of the households is and how the relationship between welfare and income inequality of those households is. The study was conducted on 12 villages which are the locations of involuntary resettlement programs with a total sample of 360 households. The study used Gini index to measure income inequality and Subjective Welfare Indicator to compare household welfare. The results showed that in general, the average household income in Koto Panjang was higher than the Provincial Minimum Wage, but it was not evenly distributed in all villages. The result also showed a negative relationship between welfare and income inequality, but it cannot be used for further analysis because the correlation value is very low.